2020
DOI: 10.32890/mmj.15.2011.8971
|View full text |Cite
|
Sign up to set email alerts
|

Role Ambiguity and Job Performance of Employees in the Service Sector SMEs in Malaysia

Abstract: Small and medium size enterprises (SMEs) play a crucial role in the economic development of Malaysia, of which the majority are in the service sector. Employees of the service sector SMEs have often been associated with low level of job performance and past research has shown that there are many factors that can contribute to employee poor performance such as role ambiguity. Thus the aim of this study was to examine the relationship between role ambiguity and job performance of employees in the service sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 76 publications
2
15
0
Order By: Relevance
“…That indicates ambiguous academic staff deal with poor academic job performance in research universities. This finding extends the previous literature on significantly and negatively relationships between role ambiguity and job performance (June & Mahmood, 2011). In the present study, the results show that academics were affected more by role ambiguity than other predictors in Malaysian research universities This finding is consistent with Ling (2014), who argues that one of the possible reasons of this similarity among academic staff is that they are less tolerant of role ambiguity due to the nature of academics performance in Malaysia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That indicates ambiguous academic staff deal with poor academic job performance in research universities. This finding extends the previous literature on significantly and negatively relationships between role ambiguity and job performance (June & Mahmood, 2011). In the present study, the results show that academics were affected more by role ambiguity than other predictors in Malaysian research universities This finding is consistent with Ling (2014), who argues that one of the possible reasons of this similarity among academic staff is that they are less tolerant of role ambiguity due to the nature of academics performance in Malaysia.…”
Section: Discussionsupporting
confidence: 92%
“…They should take into their consideration that the very explicit communication about academic staff expectation in workplace as well as establish very clear job description towards the roles. The findings of the study also confirmed the pervious research which were carried out higher ambiguity may arise due to lack of clarity regarding how to perform different academic activities of teaching and research that are necessary for the successful accomplishment of academic role (June & Mahmood, 2011;Murphy, 2014).…”
Section: Discussionsupporting
confidence: 81%
“…Warr and Inceoglu (2012) found the match between one’s personality and her job, which may be indicated by the enjoyment of the tasks, is significantly associated with her job engagement and satisfaction. June and Mahmood (2011) also found that employees with a greater level of person–job fit perform better on their tasks.…”
Section: Theory and Hypothesesmentioning
confidence: 83%
“…Nwachukwu, Žufan & Chládková, 2020), job environment, ensuring customers satisfaction (Nwachukwu, Žufan & Chládková, 2020), achieving superior organisational performance (e.g. Salau, Adeniji & Oyewunmi, 2014), investigating favouritism, (Alwerthan, 2016), technical and behavioural competence and performance evaluation (Albino, 2018), nepotism, cronyism and favouritism (Shabbir & Siddique, 2017), inclusive leadership, workplace spirituality organisational commitment and organisation citizenship behaviour (Utami, Sapta, Verawati & Astakoni, 2021; Tran & Choi, 2019), strategic leadership and business sustainability (Vu &Nwachukwu, 2020), role ambiguity, competency and person-job fit (June & Mahmood, 2011) and individual and social factors affecting occupational Accidents (Barkhordari, Malmif & Malakontikhah, 2019). The strategic value of best practice application stems from the fact that managers are endowed with discretionary decision-making power which can be exercised in health upliftment of the employees.…”
Section: Introductionmentioning
confidence: 99%